Effects of Increasing Salt Concentration on Growth Performance of 25- to 67-lb Nursery Pigs - D. Shawk; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey; S. S. Dritz; A. B. Clark (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 300 pigs (Line 241 × 600; DNA, Columbus, NE; initially 25.0 lb BW) was used in a 34-d growth trial to determine the effects of added dietary salt on the growth performance of nursery pigs weighing 25 to 67 lb. Upon entry to the nursery, pigs were allotted by BW and fed a phase 1 common starter diet (0.50% Na and 0.67% Cl) for 11 d and then a common phase 2 diet (0.35% Na and 0.59% Cl) from day 11 to 25 after weaning. At d 25 after weaning, considered d 0 in the trial, pigs were allotted by pen weight and assigned to 1 of 5 dietary treatments containing either 0.20, 0.35, 0.50, 0.65, or 0.80% salt. This corresponds to calculated dietary Na levels of 0.10, 0.16, 0.22, 0.28, and 0.34%, respectively. Calculated Cl levels were 0.23, 0.32, 0.41, 0.50, and 0.59%, respectively. A common diet containing 0.35% lb/ton salt (0.16% Na and 0.29% Cl), was then fed from d 27 to 34. From d 0 to 14, ADG, ADFI, and F/G improved (quadratic, P<0.001, 0.089, and 0.012, respectively) as added salt increased from 0.20 to 0.65%, with no further benefits observed thereafter. From d 14 to 27, there was no significant effect on ADG; however, pigs fed 0.50% added salt had numerically the greatest ADG. Average daily feed intake increased (linear, P<0.001) and F/G marginally worsened (linear, P<0.095) with increasing added salt. From d 0 to 27, ADG and F/G improved (quadratic, P<0.05 and 0.054, respectively) using up to 0.5% added salt while ADFI increased (linear, P<0.001). From d 27 to 34, when pigs were fed a common diet, there was no evidence of difference to indicate that previous dietary treatments influenced ADG; however, ADFI, and d 34 BW increased (linear, P<0.001) while F/G worsened (linear, P<0.001) with increasing salt previously fed from d 0 to 27. In conclusion, results of this study indicate that the pig’s Na and Cl requirement estimate changes and that diets for pigs weighing 25 to 45 lb, should be formulated with enough added salt to provide 0.28% Na and 0.48% Cl, which in this study was 0.65%. However, from 45 to 67 lb, 0.20% Na and .39% Cl (0.50% added salt) was sufficient to maximize growth performance.
Keywords: chloride; nursery pig; salt; sodium